MANAGEMENT APPROACH OF LOW VISION IN RETINITIS PIGMENTOSA: WHAT SHOULD WE DO? Poster Presentation - Case Report - Resident - Novi Auliya Dewi; Ani Ismail; Eva Kumalasari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinitis pigmentosa is a chronic and progressive disease throughout patient’s life. Management low vision in retinitis pigmentosa patients are to maximize their remaining vision and provision of visual aids, it can be financial dan social burden. Case Illustration : A 56-year-old man came with blurred vision in his both eyes for 12 years. The patient had cataract surgeries and IOLs implantation in 2022. Ophthalmologic examination revealed the right eye was 4/40 and the left eye was 3/60. Funduscopic examination revealed the bone spicule appearance, blood vessel attenuation, and waxy disc pallor in both eyes. Contrast sensitivity test decreased and Farnsworth hue test showed mild to severe. Humphrey visual field examination showed peripheral visual field defect, therefore patient diagnosed with low vision caused by retinitis pigmentosa with bilateral pseudophakia and his Low Vision Quality of Life was intermediate. Discussion : Treatment includes pharmacological treatment with supplementation, optical or non-optical treatment, and rehabilitation. Spectacles clarified distant and near vision with Best Corrected Visual Acuity 6/30 with photochromic lenses, for adapting the light and gave addition lens +5.00 in both eyes. Rehabilitation enhances his head tracking, scanning, and habitual spotting skills. Lighting and typoscope would help his daily reading activities as well. Conclusion : Low vision requires several management approach, patient with visual impairment can get low vision aids to optimize his visual function based on his needs. Managing low vision in patient with visual impairment has to be considered from multiple aspects.